Inoculation methods under greenhouse conditions for evaluating soybean resistance to sudden death syndrome - Neto, Austeclinio Lopes de Farias; Schmidt, Michael; Hartman, Glen Lee; Li, Shuxian; Diers, Brian Willians (Pesquisa Agropecuaria Brasileira, 2008)
The objectives of this work were to evaluate two greenhouse screening methods for sudden death syndrome (SDS) and to determine which one is best correlated with field resistance of soybean genotypes. The evaluations were done with three sets of genotypes that were classified as partially resistant, intermediate, and susceptible to SDS based on previous field evaluations. These three sets were independently evaluated for greenhouse SDS reactions using cone and tray inoculation methods. Plants were infected using grains of white sorghum [Sorghum bicolor (L.) Moench] infested with Fusarium solani f. sp. glycines. Foliar symptom severity was rated 21 days after emergence. The cone and field SDS ratings were significantly correlated and ranged from 0.69 for set 1 to 0.51 for set 3. Correlations of SDS ratings of genotypes between field and greenhouse tray ratings were significant for set 1 and not significant for set 2. The cone method showed the highest correlation with field results and is recommended to screen soybean genotypes for SDS resistance.
Keywords: Glycine max; Fusarium solani; Fusarium virguliforme; cone inoculation method; SDS; symptom severity; tray inoculation method